Shock Waves and Singular Solitary Waves for the Perturbed Cubic Boussinesq Equation (Contemporary Mathematics, 2025)
This paper recovers the shock waves and solitary wave solutions of the perturbed newly-proposed cubic Boussinesq equation. The integration scheme is the G′/G-expansion. The perturbation terms arise in various physical features in shallow water wave dynamics. The solutions are listed along with the parameter constraints for the existence of such solutions.
Keywords: shock waves, integrability, parameter constraints